A case of ductal carcinoma in situ (DCIS) with markedly elevated CA15-3 levels requiring 2 years of diagnosis - Mutsumi Fujimoto; Yoshie Kobayashi; Kazuya Kuraoka; Tomoyuki Yoshiyama; Hideo Shigematu (Surgical Case Reports)
Abstract Background CA15-3 is often elevated in breast cancer recurrence and rarely in ductal carcinoma in situ (DCIS). We report a case of DCIS with elevated CA15-3 levels, which was diagnosed after over 2 years of follow-up. Case presentation A 74-year-old woman presented with a left-sided breast mass and pain. Redness, swelling, and induration were observed in the left breast. Ultrasonography revealed a non-mass lesion in the left 3 o'clock position, skin thickening, and axillary lymphadenopathy. Serum CA15-3 levels were markedly high at 640 U/mL, suggesting inflammatory breast cancer. However, biopsies showed no malignancy. We diagnosed chronic mastitis with elevated CA15-3 levels and followed up with magnetic resonance imaging and a biopsy, as needed. Finally, DCIS was diagnosed 27 months after the first visit. She underwent a left mastectomy and a sentinel lymph node biopsy; DCIS had spread 6.5 cm and was immunohistochemically positive for CA15-3. No metastasis was found in the lymph nodes, but incidental Hodgkin lymphoma was observed. Postoperative normalization of CA15-3 levels indicated that she had DCIS with elevated CA15-3 levels. The patient underwent chemotherapy for Hodgkin lymphoma postoperatively, and there was no evidence of recurrence 1 year after surgery. Conclusion High CA15-3 levels can also be observed in DCIS, indicating that CA15-3 should not be used solely in breast cancer staging.